Loyalty, Investment Model and New Media - A Correlation Study in Banking Services in Montenegro - Bojana Femić-Radosavović; Milorad Jovović (Journal of Central Banking Theory and Practice, 2017)
In this paper we perceived causal relationship between loyalty, satisfaction, quality of the alternatives, investment size, and new media through online word of mouth in banking services in Montenegro. Obtained empirical results substantiated validity of the set hypothetical frame, i.e. meaningfulness of the conceptual model that is set.
Keywords: M39; G20; 330; Loyalty; services; banking; new media; investment model; online Word-of-Mouth (WOM).